2008
DOI: 10.1073/pnas.0809698105
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of Ebola virus production from persistent infection through activation of the Ras/MAPK pathway

Abstract: Human infections with Ebola virus (EBOV) result in a deadly viral disease known as Ebola hemorrhagic fever. Up to 90% of infected patients die, and there is no available treatment or vaccine. The sporadic human outbreaks are believed to result when EBOV ''jumps'' from an infected animal to a person and is subsequently transmitted between persons by direct contact with infected blood or body fluids. This study was undertaken to investigate the mechanism by which EBOV can persistently infect and then escape from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
62
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 71 publications
(66 citation statements)
references
References 56 publications
2
62
0
Order By: Relevance
“…12). These observations imply that paramyxovirus-resistant host cells have an elevated pAKT level but less ERK activation and that differential Ras activation modulates the permissibility to viral fusion (16,17,49). Thus, our observations establish a new framework for redefining the host cell susceptibility or resistance to a given virus and thereby reveal a novel therapeutic strategy.…”
Section: Discussionmentioning
confidence: 95%
“…12). These observations imply that paramyxovirus-resistant host cells have an elevated pAKT level but less ERK activation and that differential Ras activation modulates the permissibility to viral fusion (16,17,49). Thus, our observations establish a new framework for redefining the host cell susceptibility or resistance to a given virus and thereby reveal a novel therapeutic strategy.…”
Section: Discussionmentioning
confidence: 95%
“…In susceptible mice relative to resistant mice, genes associated with EBOV infection were differentially induced. Early in infection in the spleens of susceptible mice at day 1 p.i., we observed enrichment of p38 MAPK and ERK signaling, processes that stimulate productive EBOV infection (16, 17). Additionally we observed increased NFkB expression and induction of proinflammatory processes, which may reflect early targets of infection in the secondary lymphoid organs.…”
mentioning
confidence: 78%
“…5). Strong et al recently reported that LPS stimulation of cells persistently infected with Ebola virus led to enhanced production of virus (28). It is tempting to speculate that TLR4 triggering by LPS leads to the induction of ubiquitin ligases such as SOCS1 and TRAF6, which may then promote VLP budding due in part to their ubiquitination activity.…”
Section: Discussionmentioning
confidence: 99%